Addressing substance abuse and violence in substance use disorder treatment and batterer intervention programs - Timko Christine; Valenstein Helen; Lin Patricia Y; Moos Rudolf H; Stuart Gregory L; Cronkite Ruth C (Substance Abuse Treatment, Prevention, and Policy, 2012)
Abstract Background Substance use disorders and perpetration of intimate partner violence (IPV) are interrelated, major public health problems. Methods We surveyed directors of a sample of substance use disorder treatment programs (SUDPs; N=241) and batterer intervention programs (BIPs; N=235) in California (70% response rate) to examine the extent to which SUDPs address IPV, and BIPs address substance abuse. Results Generally, SUDPs were not addressing co-occurring IPV perpetration in a formal and comprehensive way. Few had a policy requiring assessment of potential clients, or monitoring of admitted clients, for violence perpetration; almost one-quarter did not admit potential clients who had perpetrated IPV, and only 20% had a component or track to address violence. About one-third suspended or terminated clients engaging in violence. The most common barriers to SUDPs providing IPV services were that violence prevention was not part of the program’s mission, staff lacked training in violence, and the lack of reimbursement mechanisms for such services. In contrast, BIPs tended to address substance abuse in a more formal and comprehensive way; e.g., one-half had a policy requiring potential clients to be assessed, two-thirds required monitoring of substance abuse among admitted clients, and almost one-half had a component or track to address substance abuse. SUDPs had clients with fewer resources (marriage, employment, income, housing), and more severe problems (both alcohol and drug use disorders, dual substance use and other mental health disorders, HIV + status). We found little evidence that services are centralized for individuals with both substance abuse and violence problems, even though most SUDP and BIP directors agreed that help for both problems should be obtained simultaneously in separate programs. Conclusions SUDPs may have difficulty addressing violence because they have a clientele with relatively few resources and more complex psychological and medical needs. However, policy change can modify barriers to treatment integration and service linkage, such as reimbursement restrictions and lack of staff training.